Graphene-Assisted Narrow Bandwidth Dual-Band Tunable Terahertz Metamaterial Absorber - Yan, Dexian; Meng, Miao; Li, Jiusheng; Li, Xiangjun (Frontiers in Physics, 2020)
A tunable graphene terahertz metamaterial absorber is designed by treating a monolayer continuous dumbbell-shaped structure graphene layer, which can simultaneously realize the narrow bandwidth and dual-band absorption with transverse magnetic (TM) polarization and wide incident angle operation. Two pronounced absorption peaks are caused by the novel toroidal dipole phenomenon and magnetic plasmon polariton. By optimizing the geometry parameters, the relative narrow bandwidths of the two absorption peaks are 26.4 GHz and 23.5 GHz at frequencies of 0.2242 THz and 0.5302 THz, respectively, with the absorption rate above 99.6%. Since the continuous dumbbell-shaped graphene structure is treated in the absorber, a more convenient way to realize the tuning ability by treating a bias voltage compared to the absorbers with discrete graphene structures. The designed device can work at a wide incident angles (up to 80°) under TM polarization with the absorption above 88% at low frequency. The simulation results are basically in good agreement with the results of the equivalent circuit model. This work offers huge potential applications in terahertz imaging, detecting and sensing, especially in the 6G communication systems.